Comparative ultrastructure of the spermatogenesis of three species of Poecilosclerida (Porifera, Demospongiae) - Vasconcellos, V.; Willenz, P.; Ereskovsky, A.; Lanna, E. (Zoomorphology, 2019)
The spermatogenesis of Porifera is still relatively poorly understood. In the past, it was accepted that all species presented a primitive-type spermatozoon, lacking special structures and acrosome. Nonetheless, a very peculiar spermatogenesis resulting in a sophisticated V-shaped spermatozoon with an acrosome was found in Poecilosclerida. This finding called into question the diversity and evolution of sperm cells in Poecilosclerida and in Porifera, as a whole. Is this sophisticated spermatozoon widespread in the group? We investigated here the ultrastructure of the spermatogenesis of three different species of Poecilosclerida (Demospongiae): Iophon proximum, I. piceum, and Tedania ignis. In all three species, spermatogenesis was synchronized within the spermatic cysts. Iophon proximum and T. ignis presented elongated sperm cells, but in I. piceum, their shape was oblong. A structure resembling an acrosome was only found in T. ignis. All three species presented modified spermatozoa, as in the majority of poecilosclerids investigated so far. Therefore, we are proposing that the elongated shape (modified type) of spermatozoon is the ancestral state based in the current phylogeny of Poecilosclerida and that the V-shaped sperm is only found in Crambeidae.